Arthrodesis of the digital joint using intraosseous wiring in patients with rheumatoid arthritis. Issue 1 (2nd January 2021) - Nomura, Yumi; Ishikawa, Hajime; Abe, Asami; Otani, Hiroshi; Ito, Satoshi; Nakazono, Kiyoshi; Murasawa, Akira
Abstract: Objective: Digital joints affected by rheumatoid arthritis often have severe deformity and/or dislocation, and arthrodesis in a functional position is required. Methods: Arthrodesis was performed using intraosseous wiring (modified Lister's method) from January 2011 to December 2015, and we investigated the union rate, postoperative complications, and patient satisfaction with the operation at the final follow-up. The DASH score, grip power, and pinch power were also investigated before the operation and at the final follow-up. Results: Arthrodesis was performed for 90 digital joints in 56 patients. Bone union was obtained in 85 of 89 joints (96%). Wire removal was needed due to subcutaneous protrusion in 20 joints and superficial infection in five joints. The mean preoperative DASH score of 50.5 improved to 45.2 at the final follow-up. The pulp pinch power of the index fingers through the little fingers changed significantly. In the questionnaire regarding the operated digit using a visual analogue scale (VAS, 0 [worst] to 100 [best]), the overall satisfaction was 70. Conclusion: With this approach, we achieved painless stability as well as deformity correction. A restored prehensile pattern and improvement in the activities of daily life can thus be expected after surgery.